A thousand words is worth a picture. (April 2016) - Collins, Harry; Evans, Robert
In this response to Ribeiro and Lima's paper on interactional expertise, we argue that, by not incorporating the insights of constructivist social science, their analysis goes backwards rather than advancing the debate. We show that much of the evidence they present does not lead to the conclusions they draw. We also critically examine the idea of physical contiguity, which forms a central part of Ribeiro and Lima's position. We show that its meaning is ambiguous. We conclude by suggesting that more research on the nature and influence of physical contiguity would be interesting in its own right but that it would not bear on the notion of interactional expertise.